Satellite and In-Situ Measurement for Temporal Variability of Sea Temperature in Talang Satang National Park - Nur Asilah, binti Awang (Universiti Malaysia Sarawak (UNIMAS), 2014)
Remote sensing is one of the important tools used to measure sea surface temperature (SST). The main purpose of this study is to determine sea temperature in Talang Satang National Park (TSNP) and to relate it with El Niño Southern Oscillation (ENSO). Sea temperature in TSNP is measured using HOBO Light/Temperature Data Logger and AVHRR satellite sensor. The mean sea temperature from data logger is 30.14 ± 0.74 ºC, while the sea temperature from the satellite is 29.52 ± 0.71 ºC. The reliability of SST retrieved from the satellite in TSNP is questioned. Consecutively, the satellite datasets for SST in TSNP is compared with data logger. There is high correlation between these two instruments (r = 0.792). Satellite managed to record the trends of SST, but not providing the absolute value. From the recorded trends, it shows TSNP is influenced by seasonal monsoon; namely the Northeast (NE) monsoon (November - March) and Southwest (SW) monsoon (May – September). Monsoon caused the variability of SST. High SST recorded during SW monsoon and the transitional months, but low SST during the NE monsoon. There were double maximum peak of SST every year; highest in June, followed by October. The SST in the year 2008 to 2011 were significantly different than others due to strong ENSO event. Strong ENSO event gives impact to SW monsoon, which causes significant difference (p < 0.05) in SST during these periods. Forecasting ENSO event is possible only by several months ahead. SST anomalies from previous strong El Niño episode (2009) are compared with the prediction of El Niño (summer 2014). High correlation (r = 0.614) between these anomalies indicates the incoming El Niño may affect the SST in TSNP.